SAYYED HOSSEIN NASR'S IDEAS IN THE DEVELOPMENT OF PRODUCTIVE ZAKAT IN INDONESIA: AN ANALYSIS - Lifia Lifia; Siti Masriyah; Helmi Syaifuddin (International Journal of Economics and Management Research, 2022)
The development of the modern world with all its problems in a very complex geo-politico-economy such as the gap between modernity and religion, the distribution of wealth. Sayyed Hosein Nasr is a contemporary figure who solves this modernization problem with his ideas discussing solving geo-political problems with traditionalism, perennial philosophy and integration between science and religion. This study also incorporates the ideas of Sayyed Hosein Nasr in the development of productive zakat in Indonesia in order to solve the problem of equal distribution of wealth. Productive zakat is not new in Indonesia but has many problems that need to be resolved, therefore this study is expected to be the answer to all existing problems.